2007
DOI: 10.1038/emm.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of trichostatin A-induced antiangiogenesis by small-interfering RNA for thrombospondin-1

Abstract: Abbreviations: BAE, bovine aortic endothial cell; HDI, histone deacetylase inhibitor; pTSP-Luc, luciferase reporter plasmid containing TSP-1 promoter region; siRNA, small interfering RNA; TSA, trichostatin A; TSP-1, thombospondin-1; V-DMSO, empty vector-transfected BAE cell in the presence of DMSO AbstractExpression of thrombospondin-1 (TSP-1), which is a known inhibitor of tumor growth and angiogenesis, is reciprocally regulated by positive regulators, such as VEGF. Additionally, trichostatin A (TSA) suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Thus, TSA‐mediated inhibition of Nox4‐ derived H 2 O 2 may lead to decreased expression of eNOS and regulated angiogenesis. In addition, it has been shown that HDAC inhibitors up‐regulate anti‐angigogenic genes such as thrombospondin‐1 and the VEGF competitor semaphorin III . Hence, whether Nox4 signalling is required for up‐regulation of anti‐angiogenic genes by HDAC inhibitors warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TSA‐mediated inhibition of Nox4‐ derived H 2 O 2 may lead to decreased expression of eNOS and regulated angiogenesis. In addition, it has been shown that HDAC inhibitors up‐regulate anti‐angigogenic genes such as thrombospondin‐1 and the VEGF competitor semaphorin III . Hence, whether Nox4 signalling is required for up‐regulation of anti‐angiogenic genes by HDAC inhibitors warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which valproic acid, a histone deacetylase inhibitor, enhanced the anti-angiogenic and anti-tumor effect of ABT-510 was not examined in the above studies. Other investigators have shown recently that the histone deacetylase inhibitor, trichostatin A, increases TSP-1 expression in cells propagated in vitro (116). This suggests the possibility that the increased effectiveness of ABT-510 administered with valproic acid in the above mouse models of cancer could be due to an increased expression of TSP-1 in the tumor vascular cells induced by valproic acid.…”
Section: Targets For Anti-angiogenic Therapymentioning
confidence: 99%
“…Although little is known about TSP-1-inducible chemical compounds, such a trichostatin A, SQMG is a promising candidate for the treatment of tumor-induced angiogenesis via TSP-1 upregulation. (36) …”
Section: Discussionmentioning
confidence: 99%